2019
DOI: 10.1177/0091415019871206
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Body Image Throughout the Adult Life Span: A Latent Growth Modeling Approach

Abstract: This retrospective study examined developmental trajectories of women’s body image perceptions throughout the adult life span from life course and self-discrepancy theory perspectives. Data were collected from women over 65 years of age, recruited from 15 senior communities and centers in a Midwest U.S. state in 2012. A total of 102 older women completed a survey about their past and current body image perceptions. To examine developmental trajectories of the repeated body image measures, a latent growth model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies ( Lee & Lee, 2019 b), the results of this study confirmed that subjective body size is more detrimental to body-related perceptions and behaviors than objective body size. A series of hierarchical regressions revealed significant predictive relationships between subjective body size and all criterion variables, except for BI-active, after controlling objective body size.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies ( Lee & Lee, 2019 b), the results of this study confirmed that subjective body size is more detrimental to body-related perceptions and behaviors than objective body size. A series of hierarchical regressions revealed significant predictive relationships between subjective body size and all criterion variables, except for BI-active, after controlling objective body size.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the widely accepted notion that women live longer than men ( Chrisler et al, 2016 ) and that body concerns are of greater importance for women ( Karazsia et al, 2017 ), the current study focused on female samples. However, enhanced longevity is also projected among Korean men ( Kontis et al, 2017 ), and recent studies have reported that body concerns and problems are among the most important issues affecting men ( Lee & Lee, 2019 a). Third, it is also worth noting that the proportion of people categorized as underweight based on their BMI calculation has increased in both men and women in Korea ( Park et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In girls with breast development ≥ Tanner stage II and nonmenarche (stage 2), the CSHR was positively correlated with the BSQ score, but the WHR was negatively associated with the BSQ score, which means that girls with a higher CSHR or a lower WHR were more dissatisfied with their body image. This seems to be inconsistent with the cognitive view of adult women that an "s-shaped" body is beautiful (34). Girls at the stage 2 of pubertal development have started puberty, and their female secondary sexual characteristics have begun to develop.…”
Section: Discussionmentioning
confidence: 85%